Wilker and Huygens- type inequalities for the generalized trigonometric and for the generalized hyperbolic functions - Neuman, Edward (Applied mathematics and computation, 2014)
Wilker and Huygens-type inequalities for the generalized trigonometric and hyperbolic functions are established. Main results of this paper are proven with the aid of two inequalities which involve a few parameters. For special values of the parameters obtained results simplify to the known ones which are already published in mathematical literature.